2018
DOI: 10.1007/s10803-018-3688-5
|View full text |Cite
|
Sign up to set email alerts
|

Cord and Early Childhood Plasma Adiponectin Levels and Autism Risk: A Prospective Birth Cohort Study

Abstract: Emerging research suggests that adiponectin, a cytokine produced by adipose tissue, may be implicated in ASD. In this prospective birth cohort study (n = 847), we assessed the association between cord, early childhood plasma adiponectin and the risk of developing ASD. ASD was defined based on ICD codes of physician diagnosis. Cord adiponectin levels were inversely associated with ASD risk (aOR 0.50; 95% CI 0.33, 0.77), independent of preterm birth, early childhood adiponectin and other known ASD risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
1
19
1
Order By: Relevance
“…To our knowledge, this is among the first few studies to prospectively predict mental health symptoms from cord blood adipocytokines, and the first examining a leptin-to-adiponectin ratio. The majority of research investigating cord blood adipocytokines has been primarily concerned with predicting metabolic health (Stocker & Cawthorne, 2008); however, our results provide support for the possibility that metabolic proteins at birth also forecast risk for mental health symptoms in early childhood (e.g., Li et al, 2019;Minatoya et al, 2018;Raghavan et al, 2019). Additionally, our data revealed that higher adiponectin was associated with a decreased chance of being rated higher in ability in the "managing feelings and behaviors" domain.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, this is among the first few studies to prospectively predict mental health symptoms from cord blood adipocytokines, and the first examining a leptin-to-adiponectin ratio. The majority of research investigating cord blood adipocytokines has been primarily concerned with predicting metabolic health (Stocker & Cawthorne, 2008); however, our results provide support for the possibility that metabolic proteins at birth also forecast risk for mental health symptoms in early childhood (e.g., Li et al, 2019;Minatoya et al, 2018;Raghavan et al, 2019). Additionally, our data revealed that higher adiponectin was associated with a decreased chance of being rated higher in ability in the "managing feelings and behaviors" domain.…”
Section: Discussionsupporting
confidence: 62%
“…Fetal adiponectin contributes to fetal growth both in utero and postnatally in the first years of life (Fasting et al., 2009; Mazaki‐Tovi et al., 2005, 2011), as well as early pro‐inflammatory cytokine signaling (Mcdonald & Wolfe, 2011). With regard to childhood mental health, leptin and adiponectin in cord blood have primarily been linked to neurodevelopmental symptoms in early childhood (Li et al., 2019; Minatoya et al., 2018; Raghavan et al., 2019). However, research to date has not explored whether leptin or adiponectin at birth in cord blood predict other early mental health symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Results from other rs1501299 and diabetes studies show a complex picture, rs1501299 TT genotype in ADIPOQ was known to be associated with increased risk with prediabetes in a Jordanian population (p=0.006) [13] but the G allele was significantly higher in diabetes cases than in controls in Han Chinese population [11]. Interestingly in a cord and early childhood plasma adiponectin autism study, cord adiponectin levels were inversely associated with ASD risk indicating that the lower the level of adiponectin in the plasma, the greater the risk of ASD [12].…”
Section: Discussionmentioning
confidence: 99%
“…The gene itself has an insulin-sensitizing effect and other variants of the gene are associated with body size and serum adiponectin concentrations and may also modify the risk of developing T2D [35]. Commonly, there are disturbances in adipocytokines and immunoinflammatory factors during neurodevelopment in ASD patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in immunoinflammatory factors and adipocytokines have been reported among individuals with ASD relative to age- and weight-matched TD controls [195]. Table 3 summarizes published data on adiponectin concentrations in children with ASD compared to controls [19,186,196,197]. One study reported lower serum adiponectin levels among individuals with ASD relative to age- and sex-matched healthy controls [196], but two other studies showed no significant differences [19,186].…”
Section: Emerging Factorsmentioning
confidence: 99%